Representasi Hubungan Antar-Agama Dalam Cerpen Buddhis: Sastra Sebagai Model Dialog Antar-Agama - Latifah Latifah; Ary Budiyanto (Indonesia Social Justice Network (ISJN), 2022)
The lack of inter-religion relations causes misconceptions that often lead to prejudice. Religious education from schools to higher education based on one religion alone is the cause of the low religion literacy of the other. Strict restrictions on openly discussing inter-religious topics under the pretext of SARA (Suku, Agama, Ras, dan Antargolongan [SARA]; discrimination against ethnicity, religion, race, and intergroup) in the public sphere also strengthen inter-religious barriers. As a result, knowledge about the religious life of minorities is increasingly marginalized and often leads to pressure and violence. Although not responding to the violence in an attitude that escalates the conflict. Buddhists in Indonesia seem to be trying to explain various misconceptions about their beliefs in various ways such as inter-faith seminars, music, and popular literature. In addition, Buddhist story stories also reveal Buddhist views on other religions and local traditions related to spiritual beliefs. Thus, this paper describes the representation of Buddhist view to local faith tradition, Buddhist self-explanation against the misconceptions towards their religious faith and practice, and Buddhist view towards others. In this case, this study fills the void of attention to Buddhist literature in the realm of religious literature, especially in the context of its role in interfaith dialogue